فعالية تطبيق طريقة “Qatar Debate” لتعمق مهارة الكلام في المناظرة العربية لفصل “متقدم” بدورة ناطق عربية باري كديري - Batul, Zahadatul; Rizki, Restu Budiansyah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
The design of this study is focused on measuring the effectiveness of the application of the